Positive solutions for a system of semipositone coupled fractional boundary value problems - Henderson, Johnny; Luca, Rodica (Boundary value problems, 2016)
We study the existence of positive solutions for a system of nonlinear Riemann-Liouville fractional differential equations with sign-changing nonlinearities, subject to coupled integral boundary conditions.